Respuesta :
Hi There!
What is the solution to the equation? 4y – 12 = –4 A. y = 11 B. y = 2 C. y = –4 D. y = –13
Answer:y=2
What is the solution to the equation? 4y – 12 = –4 A. y = 11 B. y = 2 C. y = –4 D. y = –13
Answer:y=2
First simplify
4y+-12=-4
Reorder the terms:
-12+4y=-4
Move all terms containing "y" to the left, all other terms to the right.
Add 12 to each side of the equation:
-12 + 12 + 4y = -4 + 12
Combine like terms:
-12 + 12 = 0
0 + 4y = -4 + 12
4y = -4 + 12
Combine like terms:
-4 + 12 = 8
4y = 8
Divide each side by '4'.
y = 2
So your answer is B Y=2
hope this helped
4y+-12=-4
Reorder the terms:
-12+4y=-4
Move all terms containing "y" to the left, all other terms to the right.
Add 12 to each side of the equation:
-12 + 12 + 4y = -4 + 12
Combine like terms:
-12 + 12 = 0
0 + 4y = -4 + 12
4y = -4 + 12
Combine like terms:
-4 + 12 = 8
4y = 8
Divide each side by '4'.
y = 2
So your answer is B Y=2
hope this helped